Displacement, Discrimination, and the Search for Care: Determinants of Nursing Home Demand Among Older Syrian Refugees - Sevim, Kaan; Sevim, Kaan (Routledge, 2026)
This study examines the demand for culturally specific nursinghomes among 408 older Syrian refugees in Istanbul. A cross-sectional survey revealed that 54% desire such facilities.Multivariate analyses show interest concentrates amongyounger-old, tertiary- educated, naturalized, and earlier-arrivalcohorts, alongside those perceiving discrimination. Conversely,the oldest-old, healthier individuals, and those intending toreturn to their origin country are less inclined. These findingsidentify priority target groups for piloting culturally specific carefacilities in Türkiye, raising awareness of older displaced adults’distinct needs.
Keywords: Discrimination; Nursing home demand; Older adult refugees; Syrian refugee